SPIRITUALITAS MENURUT PAULUS DALAM GALATIA 5:16-26: REFLEKSI TEOLOGIS PRAKTIK DISIPLIN ROHANI UMAT PERCAYA - Felix, Raynold (GENEVA: JURNAL TEOLOGI DAN MISI, 2024)
Abstract: The Apostle Paul, in the Book of Galatians 5:16-26, gives a very firm emphasis to the Galatians regarding the importance of true spirituality based on the true Gospel. This research uses a qualitative research method with an exposition research approach which aims to understand the phenomena experienced by the research subjects. The Exposition study found an explanation of what spirituality is like according to the Apostle Paul, namely: First, living not according to the desires of the flesh and second, living according to the Spirit. The implementation for the spiritual discipline practice of believers is to prioritize living according to the Spirit because otherwise the spirituality of believers will fall into legality, formality and routine. Regarding the spiritual discipline practices of believers are based and measured on the benchmark of ontological truth, namely Living According to the Spirit.Keywords: Spirituality, Reflection, Practice, Spiritual Discipline Abstrak: Rasul Paulus, dalam Kitab Galatia 5:16-26 memberikan penekanan yang sangat tegas kepada jemaat Galatia mengenai pentingnya spiritualitas yang benar di dasarkan kepada Injil yang benar. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan penelitian Eksposisi yang bertujuan untuk memahami fenomena tentang apa yang dialami oleh subyek penelitian. Kajian Eksposisi menemukan sebuah penjelasan tentang bagaimana Spiritualitas Menurut Rasul Paulus, yaitu: Pertama, Hidup tidak menurut keinginan daging dan kedua, Hidup menurut Roh. Implementasinya bagi praktik disiplin rohani umat percaya adalah lebih mengutamakan Hidup menurut Roh kerana jika tidak maka spiritualitas umat percaya akan jatuh dalam legalitas, formalitas dan rutinitas. Perihal praktik disiplin rohani umat percaya didasarkan dan diukur pada patokan kebenaran ontologis yaitu Hidup Menurut Roh. Kata Kunci: Spiritualitas, Refleksi, Praktek, Disiplin Rohani.